Influence of Social, Economic and Family Factors on Alcohol Consumption: A Systematic Review - Rubiah, Ajan; Vivien, Yew Wong Chin; Abd Hair, Awang (Malaysian Journal of Social Sciences and Humanities(MJSSH, 2021)
Alcohol consumption is increasing global and it is the reasons for large number of death. According to WHO 2018, 3.3 million deaths worldwide related to alcohol consumption was recorded in 2016 alone. The use of alcohol has a serious impact on lives which leads to poverty, road accident, injury, domestic violence and crime. This study reviews the literature to find the predictors and provide direction for future work. Using a systematic literature review, several filtering process using selected keywords a total of 20 articles were reviewed. The findings showed that most of studies were conducted in Europe followed by US. There are limited number of reviewed studies and the predictors are mainly related to socio-economic status, social factors, demographics, social networking sites, family factor and stress. Findings were discussed and direction of future work were highlighted. More studies are needed to understand the predictors of alcohol consumption in the community as large. Due to limited studies related alcohol consumption in the developing countries, topic of alcohol use are needed to be investigated in order to fill in the gap in the literature. It is important to identify and understand factors causes alcohol consumption which leads to social and health problems in the society. By identifying these predictors could reduce a potential risk when individuals are exposed to harmful behavior.